Karakteristik kimia dan sensori pai susu berbahan dasar tepung kedelai (Glycine max L.) dan serbuk daun kelor (Moringa oleifera L.) - Dewi, Indri Kusuma; Sunarmi, Sunarmi; Devian, Risnanda Vinca (Universitas Muhammadiyah Magelang, 2024)
Along with the development of science and lifestyle, causing people to prioritize processed foods that are not only filling but provide health benefits. Soy flour and moringa leaf powder can be processed because they have content that is used as a food source that is rich in protein, carbohydrates and fat. The purpose of this study was to determine the chemical and sensory characteristics of milk pie preparations made from soy flour and moringa leaf powder. This study used an observational method with a descriptive research design. This study used one formula with the main ingredients of soy flour as much as 100 grams and moringa leaf powder as much as 1,5 grams.. Pie making is done by making skin dough with soy flour as the main ingredient, olive oil as an emulsifier, powdered sugar as a flavor giver and pie filling using moringa leaf powder as a color giver, cornstarch as a thickener, powdered sugar as a flavor giver and low fat milk as a liquid ingredient, then baked at 170 ℃ for 25 minutes. The tests carried out include ash content test, moisture content test, qualitative test of protein content, carbohydrate content and fat content. The results showed that milk pies made from soy flour and moringa leaf powder had an ash content of 3,85 ± 0,42% and a moisture content of 7,17 ± 0,20%. The pies contain protein, carbohydrate and fat. The skin of the pie has a distinctive soybean smell, brownish color, sweet and savory taste and rough texture, while the contents of the pie have a distinctive smell of moringa leaves, green color, sweet taste and soft texture.